EXAMINATION OF EFFECTS OF ARTISTIC GYMNASTICS ON MORPHOLOGICAL CHARACTERISTIC OF 3TH & 4TH GRADE PUPILS OF ELEMENTARY SCHOOLS - Vesko Milenković; Dragana Aleksić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
In this work, the subject of the research is only one segment of the anthropological area, which refers to the appearance of appropriate morphological characteristic. Assessment of the examinees' morphological characteristics was conducted by the help of 13 anthropometrical measures, chosen according to the International Biologic Program (IBP), in order to cover the four dimensional area defined as longitudinal dimensionality, transversal dimensionality, volume and mass of the body and the subcutaneous fat tissue.During the 2005/06 academic year, a research was conducted so as to determine the effects of current program of physical education teaching on motor abilities flexibility of female pupils. The research involved a total sample of 107 girls from the 3th and 4th grade of elementary school. The subjects were classified in experimental and control groups. The experimental group was made of 59 students and they were practicing according to planning instruction where the artistic gymnastics had the primary part. The control group of 48 students was practicing according to official instructional plan and program for P.E. of the Republic of Serbia. At the beginning of the academic year, initial (first) measurement was performed, followed by experimental final (second) measurement at the end of experiment. The multi-variant procedures were used in this research ant those were: MANOVA, MANOCOVA and the discriminative analysis. After the experimental treatment, i.e. at the final testing, significant differences were found with female pupils in experimental and control groups concerning the 8 tests for the evaluation of morphological characteristic. The basic conclusion is that the female pupils of experimental group achieved significantly higher teaching effects than the control group, in view of partly increased morphological characteristics, being the result of the effects of the experimental treatment, as well as other external and internal factors.